Multishelled NixCo3–xO4 Hollow Microspheres Derived from Bimetal–Organic Frameworks as Anode Materials for High‐Performance Lithium‐Ion Batteries. Issue 17 (28th February 2017) - Wu, Lan‐Lan; Wang, Zhuo; Long, Yan; Li, Jian; Liu, Yu; Wang, Qi‐Shun; Wang, Xiao; Song, Shu‐Yan; Liu, Xiaogang; Zhang, Hong‐Jie
Abstract : Metal–organic frameworks (MOFs) featuring versatile topological architectures are considered to be efficient self‐sacrificial templates to achieve mesoporous nanostructured materials. A facile and cost‐efficient strategy is developed to scalably fabricate binary metal oxides with complex hollow interior structures and tunable compositions. Bimetal–organic frameworks of Ni‐Co‐BTC solid microspheres with diverse Ni/Co ratios are readily prepared by solvothermal method to induce the Ni x Co3− x O4 multishelled hollow microspheres through a morphology‐inherited annealing treatment. The obtained mixed metal oxides are demonstrated to be composed of nanometer‐sized subunits in the shells and large void spaces left between adjacent shells. When evaluated as anode materials for lithium‐ion batteries, Ni x Co3− x O4 ‐0.1 multishelled hollow microspheres deliver a high reversible capacity of 1109.8 mAh g −1 after 100 cycles at a current density of 100 mA g −1 with an excellent high‐rate capability. Appropriate capacities of 832 and 673 mAh g −1 could also be retained after 300 cycles at large currents of 1 and 2 A g −1, respectively. These prominent electrochemical properties raise a concept of synthesizing MOFs‐derived mixed metal oxides with multishelled hollow structures for progressive lithium‐ion batteries. Abstract : In virtue of the heterogeneous contraction process induced by nonequilibrium heat treatment, Ni x Co3− x O4 multishelled hollow microspheres originating from bimetal–organic frameworks are successfully achieved for high‐performance lithium‐ion batteries as anode materials. This presented strategy paves the way for a broad range of practical applications of metal–organic framework‐derived materials with multishelled hollow structures.